(untitled) - Edgar Taylor (New York, 1994)
Networking fundamentals: Commonalities among networks; Data communication considerations; Protocol fundamentals; Lower - layer; Asynchronous transfer mode (ATM); Enterprise systems connection (ESCON); Ethernet; Fiber distributed data interface (FDDI); Frame relay; Integrated services digital network (ISDN); Parallel channels...
Keywords: internet working ( telecommunication ) - handbooks, manuals,etc